Environment in the lives of children and families : perspectives from India and the UK - Phoenix, Ann; Boddy, Janet, 1969-; Walker, Catherine; Vennam, Uma (Policy Press shorts. Research., 2017)
Based on involved creative, qualitative work with families in India and the UK who live in different contexts, this book illuminates how environmental practices are negotiated within families, and how they relate to values, identities, and society.